Digital Marketing Strategies for SMEs Based on Local Wisdom in Indonesia - Rubedo, Hendar; Jusuf, Dewi Indriani; Hanna, Amida; FR, Agung Pramudya (PINISI Discretion Review, 2024)
The rapid digital transformation in the business world has created both opportunities and challenges for small and medium-sized enterprises (SMEs) in Indonesia. Given the importance of local wisdom in Indonesian culture, this study explores how digital marketing strategies can integrate cultural values. The research addresses the gap in understanding how local wisdom can enhance competitiveness in the global market, highlighting the need for innovative marketing approaches that merge tradition with modern business demands. The objective of this study is to identify effective digital marketing strategies that incorporate local wisdom to improve the performance and sustainability of SMEs in Indonesia. The study adopts a mixed-method approach, combining qualitative and quantitative data from surveys and interviews with SME owners across the retail, handicraft, and hospitality sectors. Thematic analysis and statistical tools were used to interpret the data, collected from july to december 2023. Findings reveal that SMEs integrating local wisdom in their digital marketing enjoy higher consumer engagement and brand loyalty. Key elements such as traditional values, local language, and cultural symbols significantly enhance digital campaigns. Additionally, storytelling rooted in local traditions fosters emotional connections with consumers, promoting repeat business and referrals, thereby contributing to long-term growth..